The Importance of Philosophy for Education in a Democratic Society: Editorial Essay - Snauwaert, Dale (In Factis Pax: Journal of Peace Education and Social Justice, 2012)
This essay explores the importance of philosophy for the study and practice of education in a democratic society. It will be argued that at its core education is a normative enterprise, in that it is driven by fundamental social values as well as the imperatives of social justice. These values and imperatives powerfully shape every dimension of educational theory, policy, and practice. From this perspective, education requires a normative frame of reference. Democracy, understood as not only a political system but more fundamentally as a way of life grounded in specific values and principles, provides a powerful point of reference. At the heart of democracy is the value of liberty, understood as self-determination. Self-determination requires that there should be careful reflection upon and rational deliberation concerning social values and, in turn, the imperatives of justice that inform the purposes and practices of education. It will be argued that philosophy constitutes a mode of inquiry and a discipline that enriches the capacity for reflection and rational deliberation, and hence it is essential for both democracy and the study and practice of education in a democratic society.